A MODEL FOR THE PREPARATION AND DEVELOPMENT OF LEARNING TOOLS FOR TEACHERS - Ma'ruf Al Amin (STAI Sufyan Tsauri Majenang, 2024)
Improving teacher competence through various activities such as training, workshops, seminars and mentoring must have an impact on the quality of performance both administratively (developing tools) and in organizing the learning process in the subjects taught. A profession is a promise to devote oneself to a position in the ordinary sense (task/job) because of the urge and call of conscience. It contains no compulsion, but sincerity to do wholehearted devotion. Teachers have the main task of educating, teaching, guiding, directing, training, assessing and evaluating students in early childhood education in formal education, basic education, and secondary education. Teachers as people who are responsible for the development of students to design the education and learning process based on clear references. A guideline that contains various student experiences as a reference for teachers in designing learning activities is commonly called a curriculum. Teachers are obliged to compile and develop their own learning tools, not mandatory